The Use of Canva Media in Enhancing the Interest and Writing Skills of Grade X Electrical Engineering Students - Purnamasari, Ida; Ma'fiyah, Imroatul; Lelono, Ti Wahyuni (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research investigates the effectiveness of utilizing Canva as a learning medium in enhancing procedural text writing interest and skills among 10th-grade Electrical Engineering students. Using a mixed-methods design with 36 students as research subjects, this study analyzed pre-test and post-test comparisons, and explored students' perceptions of Canva implementation. Results showed significant improvement in learning interest (32.44%) with the attraction dimension demonstrating the highest increase (57.55%). Procedural text writing ability improved significantly (t (35) = 8.74, p<0.001) with the highest effectiveness in text organization (31.25%) and content accuracy (27.45%). Thematic analysis revealed that Canva serves as a multimodal facilitator that catalyzes increased intrinsic motivation and perceived relevance of writing instruction in the technical vocational context. This research confirms Canva's potential as an effective learning medium for developing contextual writing competencies in technical vocational education.